The defining length scales of mesomagnetism: A review - Dennis, C; Borges, R; Buda, L; Ebels, U; Gregg, J; Hehn, M; Jouguelet, E; Ounadjela, K; Petej, I; Prejbeanu, I; Thornton, M (2002)
This review is intended as an introduction to mesomagnetism, with an emphasis on what the defining length scales and their origins are. It includes a brief introduction to the mathematics of domains and domain walls before examining the domain patterns and their stability in 1D and 2D confined magnetic structures. This is followed by an investigation of the effects of size and temperature on confined magnetic structures. Then, the relationship between mesomagnetism and the developing field of spin electronics is discussed. In particular, the various types of magnetoresistance, with an emphasis on the theory and applications of giant magnetoresistance and tunneling magnetoresistance, are studied. Single electronics are briefly examined before concluding with an outlook on future developments in mesomagnetism.